Compartmentalized supramolecular hydrogels based on viral nanocages towards sophisticated cargo administration. Issue 8 (13th February 2018) - Yang, Liulin; Liu, Aijie; de Ruiter, Mark V.; Hommersom, Catharina. A.; Katsonis, Nathalie; Jonkheijm, Pascal; Cornelissen, Jeroen J. L. M.
Abstract : Introduction of compartments with defined spaces inside a hydrogel network brings unique features, such as high loading efficiency, cargo quantification, stabilization and diminishment of burst release. Abstract : Introduction of compartments with defined spaces inside a hydrogel network brings unique features, such as cargo quantification, stabilization and diminishment of burst release, which are all desired for biomedical applications. As a proof of concept, guest-modified cowpea chlorotic mottle virus (CCMV) particles and complementary guest-modified hydroxylpropyl cellulose (HPC) were non-covalently cross-linked through the formation of ternary host–guest complexes with cucurbit[8]uril (CB[8]). Furthermore, CCMV based virus-like particles (VLPs) loaded with tetrasulfonated zinc phthalocyanine (ZnPc) were prepared, with a loading efficiency up to 99%, which are subsequently successfully integrated inside the supramolecular hydrogel network. It was shown that compartments provided by protein cages not only help to quantify the loaded ZnPc cargo, but also improve the water solubility of ZnPc to avoid undesired aggregation. Moreover, the VLPs together with ZnPc cargo can be released in a controlled way without an initial burst release. The photodynamic effect of ZnPc molecules was retained after encapsulation of capsid protein and release from the hydrogel. This line of research suggests a new approach for sophisticated drug administration in supramolecular hydrogels.